FUNGSI FILSAFAT PENDIDIKAN TERHADAP ILMU PENDIDIKAN ISLAM - Ruhaya, Besse (Universitas Islam Negeri Alauddin Makassar, 2022)
This research is entitled the function of the philosophy of education in Islamic education with the aim of providing additional scientific insight about the function of the philosophy of education in the science of education. The research method used is a library research method or reading results as a secondary source contained in books and scientific journal articles. The data in each book or article is then sorted according to its relevance and an analysis of the content is carried out to see its suitability. Finally, the author concludes on all the information or data that has been collected. The function of the philosophy of education for Islamic education is to direct and provide a systematic, deep, logical, universal, and radical rationale for various problems that can be operated in the field of education, which uses no other reference to the Koran and al-Hadith.Functions, Philosophy of Education, and Science of Islamic Education